HUBUNGAN KAUSALITAS ANTARA PERDAGANGAN INTERNASIONAL, INDUSTRIALISASI DAN PEMBANGUNAN EKONOMI BERKELANJUTAN DI ASIA - Meiske Marisa Fafan Titaley (Politeknik Negeri Ambon, 2026)
Introduction: This investigation examines the intricate causal nexus among international trade liberalization, industrial transformation, and sustainable economic advancement across Asian countries from 2000 to 2023.Methods: Employing panel data regression methods, including fixed-effects models, this quantitative inquiry analyzes secondary datasets from the World Bank's Development Indicators and the Asian Development Bank, incorporating Granger causality testing and impulse-response function analysis across Southeast and East Asian nations.Results: Empirical evidence reveals bidirectional causality between trade openness and industrialization, with coefficients of 0.347 (p<0.01), demonstrating reciprocal reinforcement mechanisms. Industrialization has dual effects on sustainability dimensions: it increases human development indices by 0.428 percent while simultaneously increasing carbon emissions by 0.561 percent per 1 percent increase in manufacturing value added. Threshold analysis identifies a critical inflection point at USD 8,500 per capita GDP where industrialization-environment trajectories reverse, corroborating Environmental Kuznets Curve hypotheses. Variance decomposition indicates trade liberalization explicates 34.7 percent of industrial variation, while industrialization accounts for 28.4 percent of sustainability outcome fluctuations.Conclusion: Findings necessitate recalibrating policy toward integrative frameworks that harmonize trade expansion, sustainable industrial upgrading, and ecological preservation through green technology adoption and strengthened regional institutional governance. Keywords: Asian Economies, Economic Development, Environmental Sustainability, Sustainable Industrialization, Trade Liberalization